Low-Loading of Pt Nanoparticles on 3D Carbon Foam Support for Highly Active and Stable Hydrogen Production - Ghanim, Abdulsattar H.; Koonce, Jonathan G.; Hasa, Bjorn; Rassoolkhani, Alan M.; Cheng, Wei; Peate, David W.; Lee, Joun; Mubeen, Syed (Frontiers in Chemistry, 2018)
Minimizing Pt loading is essential for designing cost-effective water electrolyzers and fuel cell systems. Recently, three-dimensional macroporous open-pore electroactive supports have been widely regarded as promising architectures to lower loading amounts of Pt because of its large surface area, easy electrolyte access to Pt sites, and superior gas diffusion properties to accelerate diffusion of H2 bubbles from the Pt surface. However, studies to date have mainly focused on Pt loading on Ni-based 3D open pore supports which are prone to corrosion in highly acidic and alkaline conditions. Here, we investigate electrodeposition of Pt nanoparticles in low-loading amounts on commercially available, inexpensive, 3D carbon foam (CF) support and benchmark their activity and stability for electrolytic hydrogen production. We first elucidate the effect of deposition potential on the Pt nanoparticle size, density and subsequently its coverage on 3D CF. Analysis of the Pt deposit using scanning electron microscopy images reveal that for a given deposition charge density, the particle density increases (with cubic power) and particle size decreases (linearly) with deposition overpotential. A deposition potential of −0.4 V vs. standard calomel electrode (SCE) provided the highest Pt nanoparticle coverage on 3D CF surface. Different loading amounts of Pt (0.0075–0.1 mgPt/cm2) was then deposited on CF at −0.4 V vs. SCE and subsequently studied for its hydrogen evolution reaction (HER) activity in acidic 1M H2SO4 electrolyte. The Pt/CF catalyst with loading amounts as low as 0.06 mgPt/cm2 (10-fold lower than state-of-the-art commercial electrodes) demonstrated a mass activity of 2.6 ampere per milligram Pt at 200 mV overpotential, nearly 6-fold greater than the commercial Pt/C catalyst tested under similar conditions. The 3D architectured electrode also demonstrated excellent stability, showing <7% loss in activity after 60 h of constant current water electrolysis at 100 mA/cm2.